(3eHGOF GdNWQ hGdJCejf (B/s - (3GdgGfS, eNJGQ eMehOs; (3MehOI, GHQGgje YHOGdfHj s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2001)
(3GdNWQ hGdJCejfGJ GdELJeGYjI ,aj bjGS GdNWQ hEOGQJg aj GdEWGQ GdYGe ddJCejf ,GdbGfhf GdLOjO ddJCejfGJ GdELJeGYjI ,GdCejf Ydi GdMjGI ,LOhGhd hEMJeGdGJ GdMjGI ,MSGH GdCbSGW GdhMjOI GdUGajI dhKGFb JCejf GdMjGJ HCfhGYgG ,GdCbSGW GdSfhjI GdUGajI dhKGFb JCejf GdMjGIs
Keywords: (3GdJCejfs; (3GdNWQs